2011
DOI: 10.1186/1471-2407-11-16
|View full text |Cite
|
Sign up to set email alerts
|

Can Bcl-XL expression predict the radio sensitivity of Bilharzial-related squamous bladder carcinoma? a prospective comparative study

Abstract: BackgroundLocal pelvic recurrence after radical cystectomy for muscle invasive bilharzial related squamous cell carcinoma accounts for 75% of treatment failures even in organ confined tumors. Despite the proven value of lymphadenectomy, up to 60% of patients undergoing cystectomy do not have it. These factors are in favor of adjuvant radiotherapy reevaluation. objectives: to evaluate the effect of adjuvant radiotherapy on disease free survival in muscle invasive bilharzial related squamous cell carcinoma of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Adjuvant radiotherapy has historically been associated with serious side-effects including intestinal obstruction and urinary fistulae. In B-SCC, a recent study of patients determined that those not receiving adjuvant radiotherapy had a DFS of 29% compared to 48% for those who received adjuvant radiotherapy [41] . Given advances in radiation techniques and other promising contemporary studies of B-SCC [42] , postoperative radiotherapy for SCC should also be revisited.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant radiotherapy has historically been associated with serious side-effects including intestinal obstruction and urinary fistulae. In B-SCC, a recent study of patients determined that those not receiving adjuvant radiotherapy had a DFS of 29% compared to 48% for those who received adjuvant radiotherapy [41] . Given advances in radiation techniques and other promising contemporary studies of B-SCC [42] , postoperative radiotherapy for SCC should also be revisited.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that multiple signal transduction pathways, including the PI3K/AKT, MAPK/ERK, ATM and EGFR pathways, can reduce radiation efficacy by promoting DNA repair in tumor cells (34, 35). Overexpression of Bcl2 and Bcl-XL resulted in resistance of tumor cells to apoptosis induced by radiation (3639). Here we discovered that radiation induces activation of the JAK2/STAT3 survival signaling pathway, leading to upregulation of its downstream transcriptional effectors, Bcl2/Bcl-XL, in various human lung cancer cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The typical patient with NRAS mutant melanoma tends to be older (>55 years of age) with a more chronic pattern of UV exposure than a patient with a BRAF mutant melanoma (33, 34). Overall, patients with NRAS mutant melanomas have been found to have thicker tumors at presentation.…”
Section: Clinical and Prognostic Significance Of Nras Mutations In Mementioning
confidence: 99%